Analisis Kinerja Pegawai Di Balai Pengembangan Pendidikan Anak Usia Dini Dan Pendidikan Masyarakat (Bp-Paud Dan Dikmas) Sumatera Utara - Samosir, Yanne Dian Sri Anggreini; Warjio, Warjio; Purba, Amir; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
Based on the background of the problem, the formulation of the problem in the study is How is the performance of Employees at BP-PAUD and Dikmas North Sumatra. What factors are obstacles to the performance of Employees at BP-PAUD and Dikmas North Sumatra. The research objective was to analyze the performance of employees at BP-PAUD and Dikmas North Sumatra. Obstacle factors for employee performance at BP-PAUD and Dikmas North Sumatra. The research method used was descriptive with qualitative analysis. Data collection was obtained from interviews, documentation and observation. The results of the study are the productivity of BP-PAUD and DIKMAS has shown maximum results, this is evidenced by the standard of service provided and then added with the direct supervision provided by the Head of Section to employees. Responsibility for the performance of good BP-PAUD and DIKMAS employees can be seen from several aspects such as the quality of work obtained, a sense of responsibility for the tasks assigned, and good cooperation with other employees. In addition, the response from the learning staff must be responded to because all responses can be benchmarks or references to obtain better performance. While the suggestions from the research are Giving a proposal to the Government regarding this matter so that the number of human resources can be added. The existence of strict sanctions against negligence of employee responsibilities in carrying out their work. Completing or fulfilling facilities and infrastructure for employees.